Content validity of the Islamic emotional regulation Module - Mohd Izwan Mahmud; Joki Perdani Sawai; Rezki Perdani Sawai; Masturina Mahazir; Shamsuritawati Sharif (Human Resource Management Academic Research Society (HRMARS), 2022)
This study aimed to assess the content validity of the Islamic Emotional Regulation Module towards the mental wellbeing of youth. This module has five main submodules, namely the emotional regulation submodule of sadness, anger, guilt, shame and fear. This module has gone through content validation involving five experts in the fields of Islamic thought, moral psychology and adolescent counseling. Data evaluation by experts were analyzed using Content Validity Index (CVI). The results of the evaluation by experts showed that all modules tested had a high content validity coefficient of between .770 to .810 (> .70). The results of the study concluded that all submodules of the Islamic Emotional Regulation Module have high content validity and a pilot study should be conducted to determine the reliability of the modules before being used in the experimental study. It is hoped that this developed module can help the youths in regulating their emotions as well as becoming useful human beings. An individual’s ability to regulate emotions can help them manage and respond effectively to the emotional experiences they experience. The suggestion follow up study is to conduct a pilot study to determine the reliability of the module and test the effectiveness of the module in a larger population.